PENGARUH FAKTOR-FAKTOR KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KINERJA GURU - Ni Komang Safitri Carina (Widyadari : Jurnal Pendidikan, 2018)
This study has the main objective of knowing the influence of transformational leadership factors consisting of charisma, intellectual stimulation, and individualized consideration either simultaneously or partially to the performance of SMK Guru Nusa Dua Toya Anyar Bali. In this study also aims to determine whether the individualized consideration has the most dominant influence on the performance of teachers SMK Nusa Dua Toya Anyar Bali. Variables in this study consisted of three independent variables: Charisma (X1), Stimulation (X2), and Attention (X3), and Teacher Performance (Y). From the results of the analysis there is a significant influence between charisma, intellectual stimulation, and individually individualized consideration on the performance of teachers at SMK Nusa Dua Toya Anyar Bali. This is supported by the test result F arithmetic = 167,804 at a significant level of 0.000 which is smaller than α = 0.05. This means the efforts made by the leader of the teacher at SMK Nusa Dua Toya Anyar Bali in order to improve its performance by applying the symbols in transformational leadership work well. There is an influence between charisma, intellectual stimulation, and individualized consideration partially to the performance of teachers of SMK Nusa Dua Toya Anyar Bali, proved true. This proof is based on the t value and significance level of the three independent variables, which is below 5%, so it can be said charisma, intellectual stimulation, and individualized consideration partially influence the performance of teachers in SMK Nusa Two Toya Anyar Bali. From the results note that the individualized Attention Variables have the highest value of titung with a value of 14.263. This proves that the individualized Variables of Attention have the most dominant influence on teacher performance in SMK Nusa Dua Toya Anyar Bali.